Padlet as a Creative Wall for Enhancing and Evaluating Students’ Writing of Recount Text in a Higher Education - Dian Fadhilawati; Dwita Laksmita Rachmawati; Sri Hastari (Jurnal Sinestesia, 2022)
The purposes of this research were to enhance the students’ writing of recount texts especially personal recounts by applying Padlet and to know their responses to the use of Padlet as a medium to learn and evaluate recount text especially personal recounts at a private university in Blitar. The researchers utilized classroom action research, which covered four steps; 1) planning, 2) acting, 3) observing and evaluating, and 4) reflecting. Tests and questionnaires were utilized to gain the data. The research results proved that the use of Padlet as a medium to learn the writing of recounts text could enhance the students' learning outcomes from the preliminary test by 59.84, increasing to 81.26 in the post-test. Furthermore, the students also presented a positive attitude toward the use of Padlet in teaching and learning writing of personal recounts text. Based on the findings, teachers may choose to use Padlet as an alternative tool for creating a creative wall of materials as well as assessing the students when instructing writing.